Clinical and immunological characteristics of bacterial pneumonia associated with HIV infection coupled to drug addiction - L. V. Puzyreva (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Bacterial pneumonia holds the second place after respiratory tuberculosis in patients with HIV infection. In recent years, sexual transmission of HIV was replaced by injection drug route. It seems of high relevance to advance medical aid to patients with HIV infection and bacterial pneumonia depending on psychoactive substance use.Aim of study — assessment of clinical and immunological manifestations of bacterial pneumonia coupled to HIV infection with respect to verified injection drug use.Materials and methods. Clinical and immunological data collected from 224 patients with HIV infection and pneumonia were retrospectively analyzed: group 1 group — 70 patients with HIV infection, IDU, verified bacterial pneumonia; group 2 — 16 injecting drug users (IDU) with HIV infection and pneumonia of unverified etiology; group 3 — 65 patients with HIV and bacterial pneumonia of verified etiology without injection drug use, group 4 — 73 patients with HIV infection and bacterial pneumonia of unverified etiology, without injection drug use. The data obtained were analyzed by using software Statistica 13.3. Methods of descriptive statistics with calculation of nonparametric criterion — the Kruskall—Wallis test (H-criterion) and χ2 test — were used.Results. Immunological manifestations of HIV infection and bacterial pneumonia were characterized by decreased count of CD4+ cells paralleled with increased count of CD3+ and CD8+ cells at higher magnitude without injection drug use being also featured with peak viral load upon developing pneumonia. Bacterial pneumonia coupled to HIV infection showed clinical manifestations similar both in injecting drug users and non-users, proceeding in 10% cases during normothermia. Injection drug user patients often demonstrated clinical picture of pneumonia resembling those found in sepsis such as pain in the body, muscles, bone aches untypical to HIV-sexually infected subjects. In addition, systolic murmur on a heart top was more often auscultated in this patient group.Conclusion. Subjects self-considered healthy being at risk of sexually transmitted infections should examined for HIV. All subjects manifested with symptoms of the lower airway tract infections in admission department should not be rejected to be hospitalized and undergo chest X-ray examination.